The effect of bottom ash (BA) as partial sand replacement on concrete compressive strength and workability - Nurul Fazilawani , Mohamad (2013)
Coal combustion by-product has been around since people understood that burning coal can generates electricity, and its utilization in concrete production for nearly a century. Malaysia facing an increasing production using by-products called coal bottom ash from thermal power plants, running into method of disposal where no other commercial usage. A significant amount of research has been conducted somewhere on coal bottom ash to ascertain its pozzolanic activity, compressive strength in concrete and mortar, durability and water absorption characteristics in order to ensure its usage as a construction material. This paper presents the experimental investigations carried out to study the effect of bottom ash as partial sand replacement on concrete compressive strength and workability. The various properties was studied consist of compressive strength, workability and water absorption of the concrete at the various percentage of replacement. The strength development for various percentages varies from 0%, 10%, 20%, 30 1/o, 40% and 501/o with bottom ash can easily be equated to the strength development of normal concrete at various ages. The results of compressive strength at 7, 28, 60 and 90 days curing are presented. The results showed that for a grade 30 concrete with a combination of coal bottom ash can produce 28 day strength similar to normal concrete. replacement of fine aggregates